HUBUNGAN TAHAP PERKEMBANGAN KELUARGA DAN POLA ASUH ORANG TUA TERHADAP PERILAKU SEKSUAL PADA REMAJA - Bernadetha, Bernadetha; Asmarawanti, Asmarawanti; Marcelina, Sheilla Tania; Nukuhaly, Hasnawati; Situmeang, Lamria (Ensiklopedia of Journal, 2024)
Sexual behavior is something that is considered to influence self-esteem behavior, parent-child relationships, sexual thrill-seeking tendencies, the presence of deviant peers and the use of pornographic media. The family development stage begins when the first child turns 13 years old and usually ends 6-7 years later, when the child leaves the parental home. Parenting can be defined as all the ways parents treat their children. The purpose of the study was to find the relationship of family development stages and parenting patterns to sexual behavior. The design of this study was cross sectional with a population of 152 samples of 110 respondents with proportional randam sampling technique. Data analysis used is univariate and bivariate. The results of the study with statistical tests showed the value of family development stages p value 0.000 and parenting patterns p value: 0.000 where both are smaller than alpha (p <0.05). The conclusion is that there is a significant relationship between the stage of family development and parenting on sexual behavior. The recommendation of the results of this study is that respondents get good fulfillment of adolescent age developmental tasks and friendly parenting so that they can control sexual behavior in themselves and know the dangers of risky sexual behavior.Keywords: Family Development, Parenting, Sexual Behavior